Concentrations of trace elements in American alligators (Alligator mississippiensis) from Florida, USA - Horai, Sawako; Itai, Takaaki; Noguchi, Takako; Yasuda, Yusuke; Adachi, Haruki; Hyobu, Yuika; Riyadi, Adi S.; Boggs, Ashley S.P.; Lowers, Russell; Guillette, Louis J.; Tanabe, Shinsuke (Chemosphere (Oxford), 2014)
•We report an effect of trace elements on American alligators from NASA activities.•Fe concentration from MINWR (NASA activity area) was higher than other areas.•Fe levels of some individuals from MINWR exceed threshold value for toxic effects.•As and Se levels in 2009 increase compared with 1999 in Florida. Concentrations of 28 trace elements (Li, Mg, Al, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, As, Se, Rb, Sr, Mo, Ag, Cd, In, Sn, Sb, Cs, Tl, Hg, Pb, and Bi) in the livers of juvenile and adult American alligators inhabiting two central Florida lakes, Lake Apopka (LA), and Lake Woodruff National Wildlife Refuge (LW) and one lagoon population located in Merritt Island National Wildlife Refuge (MINWR; NASA), were determined. In juveniles from MINWR, concentrations of nine elements (Li, Fe, Ni, Sr, In, Sb, Hg, Pb and Bi) were significantly higher, whereas six elements (V, Fe, As, Sr, Hg and Bi) were elevated in adults (p<0.05) obtained from MINWR. Significant enrichment of some trace elements in adults, relative to juveniles, was observed at all three sampling areas. Specifically, Fe, Pb and Hg were significantly elevated in adults when compared to juveniles, suggesting age-dependent accumulation of these elements. Further, As, Se and Sn showed the same trend but only in animals collected from MINWR. Mean Fe concentrations in the livers of adults from LA, LW and MINWR were 1770μgg−1 DW, 3690μgg−1 DW and 5250μgg−1 DW, respectively. More than half of the adult specimens from LW and MINWR exhibited elevated hepatic Fe concentrations that exceed the threshold value for toxic effects in donkey, red deer and human. These results prompted us to express our concern on possible exposure and health effects in American alligators by some trace elements derived from NASA activities.